Utility of video capsule endoscopy in clinical practice, experience at King Faisal Specialist Hospital and Research Center, Riyadh - Aljemeeli, Feras A.; Alzead, Ahmed A.; Shareef, Saad Al; Almuhaidb, Aymen; Khan, Mohammed Q.; AlQaraawi, Abdullah; Al-Ashgar, Hamad I.; Al-Kahtani, Khalid; Al Quaiz, Mohammed; Alsohaibani, Fahad; Alfadda, Abdulrahman; Almahrouq, Adnan; et al. (International Journal of Advances in Medicine, 2022)
Background: Video capsule endoscopy (VCE) is a valuable diagnostic tool for the evaluation of the small intestine. Evidence shows that it is effective in the diagnosis of occult bleeding and superficial lesions that are not radiographically observed. We evaluated the efficacy and safety of the capsule endoscopy in the diagnosis and management of the common gastrointestinal disorders. Methods: A retrospective chart review of a total of 326 candidates who have met the inclusion criteria and who underwent VCE from the period from January 2006 till December 2018. Results: The main indication for Video Capsule Endoscopy was small bowel overt gastrointestinal bleeding with 106 cases (32.6%) followed by iron deficiency anemia with 104 cases (32%). Capsule retention rate was observed in 11 cases (3.4%) 4 of which were crohn’s disease patients (22.2%). Overall diagnostic yield was 36%, 64% for overt gastrointestinal bleeding and 41% for occult gastrointestinal bleeding. The most common reported positive finding was Angiodysplasia in 19.9% of cases, followed by ulcers in 13.8% of cases, followed by polyps in 8.3% of cases and erosions in 8% of cases. Conclusions: Video capsule endoscopy proved to be an essential diagnostic tool in gastrointestinal bleeding. Advantages of VCE include; less labor, higher resolution examination of mucosa, relative safety, and noninvasiveness. On the other hand, it does not offer intervention capabilities when compared with enteroscopy and its interpretation was sometimes difficult and time consuming. Risk of capsule retention remains significant especially in patients suffering from crohn’s disease.